Teologia i duszpasterska funkcja sanktuarium. Zagadnienia wybrane - Żądło, Andrzej (Studia Pastoralne, 2026)
At the beginning of this article, we stated that the sanctuary is not only a hieron, or temple as such, a temple like many others, but it is naos, or place of God’s special presence, a place specially chosen by him and for this reason exceptional for us. If today we are remembering these elementary matters that should characterize every temple, we do it because we need to draw patterns from the sanctuaries. „While the reform of the Liturgy desired by the Second Vatican Council, can be considered already in progress, the pastoral promotion of the Liturgy constitutes a permanent commitment to draw ever more abundantly from the riches of the Liturgy that vital force which spreads from Christ to the members of his Body which is the Church” (John Paul II, Apostolic Letter Vicesimus quintus annus, No. 10). We wanted to not only recall the theology of the sanctuary, but also to draw the attention of the readers to the fact that there is still a great work to do in the field of well-understood and organized liturgical pastoral care – especially with regard to sanctuaries. Much in this area – as we have tried to show in the course of this study – is to be done. In this work, however, we count on a model and appealing example of our sanctuaries. If sanctuaries are to play an important role in the life of the Church, they should be properly organized in terms of the personal, local, and liturgical. Let us wish that they are really organized and that they can radiate to the whole Church through the pilgrims who come to them. Veneration in our shrines must be revived and aroused. In the case of some sanctuaries, the pilgrimages organized for them have already disappeared. And sanctuaries fulfill their function only when they attract pilgrims. Therefore, the conviction that veneration in sanctuaries should be enlivened by organizing pilgrimages to them on various occasions is of particular importance.